TINJAUAN YURIDIS TERHADAP ANAK SEBAGAI KORBAN TINDAK PIDANA PENCABULAN DAN PERSETUBUHAN (Studi Putusan Nomor 141/Pid.Sus/2026/PN Srg) - Irwan Sapta Putra; Mohammad Hifni; Najma Nurapriliani (Gapenas Publisher, 2026)
Children are a trust and blessing from God Almighty who have the right to be protected from all forms of violence, including sexual molestation and sexual intercourse crimes. However, the increasing number of sexual violence cases against children indicates that the existing legal protection has not been fully effective in preventing such crimes. This study aims to analyze the legal protection provided to children as victims of sexual molestation and sexual intercourse crimes and to examine the judges' legal considerations in Court Decision Number 141/Pid.Sus/2026/PN Srg based on the applicable laws and regulations. This research employed a normative legal research method using a statutory approach, a case approach, and a conceptual approach. The legal materials consisted of primary, secondary, and tertiary legal sources collected through library research. The data were analyzed qualitatively using a deductive method. The results indicate that legal protection for children as victims of sexual molestation and sexual intercourse crimes has been regulated under the 11415 Constitution of the Republic of Indonesia, Law Number 35 of 2014 concerning Child Protection, Law Number 12 of 2022 concerning Sexual Violence Crimes, and other related legislation. Such protection includes legal assistance during judicial proceedings, medical and psychological rehabilitation, protection of victims' identities, and the restoration of victims' rights. Based on the normative analysis of Court Decision Number 141/Pid.Sus/2026/PN Srg, judges' legal considerations in cases involving sexual crimes against children should comprehensively address juridical, philosophical, and sociological aspects while prioritizing the principle of the best interests of the child. Furthermore, judicial decisions are expected not only to provide legal certainty through the imposition of criminal sanctions upon offenders but also to ensure justice and legal benefits by guaranteeing optimal protection and recovery for child victims.